Productive Waqf Development in Improving Islamic Boarding School Independent Economics - Saiful Bakhri; Hainnuraqma Binti Rahim; Fuadah Johari (Program Studi Perbankan Syariah Sekolah Tinggi Agama Islam Salahuddin Pasuruan, 2024)
Non-Index Publication